An Analysis of Character Values in English Textbook for Seventh Grade Students Entitled When English Rings The Bell (Revised 2016) - Aprisa Marise Aminingsi (Yayasan Karinosseff Muda Indonesia, 2021)
This study aims to investigate the values of characters in the 2013 curriculum in English textbook students at seventh grade students entitled